O papel da cirurgia bariátrica na regulação do sono e comportamento alimentar em adultos obesos - Rique, Gabriela Lemos Negri (2020)
Obesity currently represents one of the greatest threats to human health, being the target of numerous therapeutic approaches. Bariatric surgery is the most effective form of intervention in morbid obesity, causing long-term effective weight loss and improvement in comorbidities. Among the various surgical techniques used, vertical gastrectomy (GV) stands out as the fastest growing procedure in Brazil and in the world, being released as a relatively recent single procedure in Brazil. Studies evaluating the impact of this surgery in the short, medium and long term are scarce in our country, especially with regard to the effects on sleep, eating behavior and metabolic parameters of the individuals submitted to it. In this perspective, the present study aimed to verify the short-term impact (1st and 4th postoperative month) of GV on sleep, eating behavior and metabolic parameters of obese patients undergoing this procedure. Using a quasi-experimental, descriptive and analytical design, 14 volunteers (6 men and 8 women aged 21 to 48 years, M = 35.57; SD = 7.33) were submitted to GV participating in two moments of the research: stage preoperative (1st week before surgery) and postoperative (1st and 4th month after surgery). To assess the clinical and metabolic parameters of the participants, laboratory tests, the standard questionnaire for identifying chronotypes, the Pittsburgh Sleep Quality Index questionnaire, the Epworth Sleepiness Scale, the Night Eating Syndrome Questionnaire, the Periodic Eating Compulsion Scale were used. The results demonstrated a negative and significant correlation between the night eating syndrome (SCN) and the percentage of excess weight loss (% PEP) in the 1st postoperative month (PO) (Rô = -0.75; p = 0.019). In the 4th PO month there was an improvement in sleep quality with a significant reduction in the total sleep quality score (Z = -2.01; p = 0.023) and also a statistically significant reduction in excessive daytime sleepiness (Z = -2.20; p = 0.016). There was also a significant decrease in the total score of the binge eating scale (Z = -2.38; p = 0.008) in this period. There were no significant changes in the glycemic and lipid profile between the 1st and 4th PO months, however, a statistically significant reduction in liver enzymes (AST / ALT), BMI and% PEP was observed. The results showed that GV positively affects sleep quality and excessive daytime sleepiness, as well as symptoms of binge eating and transaminases (AST / ALT) within the 4th month after surgery. In addition, it was found that the SCN hinders the percentage weight loss in the 1st PO month, demanding greater attention. These findings suggest that GV can cause significant and beneficial changes on sleep, eating behavior and liver function in obese patients in the 4th month after the surgical procedure, contributing to a better quality of life and reduction of morbidity and mortality in this population.